Tyrosinase Inhibition, Antiglycation, and Antioxidant Activity of Xylocarpus granatum - Irmanida Batubara; Maily Mustofa; Wulan Tri Wahyuni; Kilala Tilaar; Waras Nurcholis; Fransiska Devy Junardy; Yogo Suro Priyadi; Erna Subroto; Saat Egra; Nevianti Zamany (Biosaintifika: Journal of Biology & Biology Education, 2020)
Xylocarpus granatum is mangrove plant that traditionally used as face powder in Central Sulawesi, Indonesia which related to antioxidant, antiglycation and tyrosinase inhibition activities. This study aimed to evaluate the potency of X. granatum as a tyrosinase inhibitor, antiglycation, and antioxidant. The leaves, stem, stem bark, fruit flesh, fruit peel, and kernel of X. granatum were extracted using ethanol then their tyrosinase inhibition, antiglycation, and antioxidant were evaluated. Tyrosinase inhibition activity was evaluated using in vitro assay with L-tyrosine and L-DOPA as the substrate of monophenolase and diphenolase. Antiglycation activity was studied by measuring the excitation and emission fluorescence from glucose and fructose reaction with Bovine Serum Albumin. Antioxidant activity was measured using the DPPH radical scavenging assay. The result showed that the ethanolic extract of fruit flesh has higher potency as tyrosinase inhibitor (IC50 of 393.8 mg/L and IC50 of 448 mg/L, respectively for monophenolase and diphenolase). Antiglycation assay showed that the ethanolic extract of stem bark provides the strongest antiglycation activity with an IC50 of 118.1 mg/L. Meanwhile, fruit peel provides the strongest antioxidant activity with an IC50 of 5.5 mg/L. Fractionation of ethanolic extracts of each part of X. granatum tree yield fractions with lower bioactivity compared to the crude extract. Moreover, stem extract and fractions from two different locations (Tarakan and Kendari) tend to have different bioactivities strengths.Â  The stem part of X granatum could be developed as new raw material of cosmetic product in Indonesia, while ethanol as the solvent for extraction, and the different bioactivity of stem extract from different location can be the consideration for the industry to standardize the extract prior to production of final product.